2001
DOI: 10.1002/pits.1022
|View full text |Cite
|
Sign up to set email alerts
|

Sorting out successful failures: Exploratory analyses of factors associated with academic and behavioral outcomes of retained students

Abstract: This prospective longitudinal study followed a sample of 106 kindergarten students through 11th grade examining the effects of family characteristics, school readiness, socialization, and student demographics on academic achievement and behavioral adjustment outcomes. These educational outcomes were contrasted among four groups consisting of: 1) early grade retainees; 2) transitionally placed retained students; 3) students recommended for transitional placement, but promoted; and 4) regularly promoted students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 39 publications
2
27
1
1
Order By: Relevance
“…One may assume that highly educated mothers more readily encourage their children's development of these skills. These results support those of other studies emphasizing the impact of mothers' education on their children's academic success and behavioral adjustment outcomes (Ferguson, Jimerson, & Dalton, 2001;Loeb, Fuller, Kagan, & Carrol, 2004;Ramey-Craig & Landesman, 1999).…”
Section: Sociodemographic Impact On Lotca Scoressupporting
confidence: 89%
“…One may assume that highly educated mothers more readily encourage their children's development of these skills. These results support those of other studies emphasizing the impact of mothers' education on their children's academic success and behavioral adjustment outcomes (Ferguson, Jimerson, & Dalton, 2001;Loeb, Fuller, Kagan, & Carrol, 2004;Ramey-Craig & Landesman, 1999).…”
Section: Sociodemographic Impact On Lotca Scoressupporting
confidence: 89%
“…(Hoover-Dempsey, Bassler and Brissie, 1987, Lareau, 1987, Delgado-Gaitan, 1992, Ecless & Harold, 1993, Pena, 2000 In their research through which the relationship between the neuro-cognitive development of children enrolled in kindergarten and their socio-economic status are studied, Noble, Norman and Farah (2005) found out that socio-economic status and cognitive function have an impact on language, visual perception, visual spatial relations and memory. Ferguson, Jimerson and Dalton (2001) noted in their study that socio-economic status, education level of mother, educational values of family, social emotional functions in kindergarten and age are significant factors for children falling behind their peers and therefore these factors affects academic and behavioral skills. Martin, Sewel and Manni (1977) studied the effects of race and social class on development of visual motor integration in children enrolled in preschools and it is reported that children of white race and at high socio-economic status have more advanced visual motor development when compared to children of black race and at low socio-economic status.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers find that repeating a grade is strongly correlated with the poor performance in mathematics and reading tests of repeaters (Holmes 1989;Ferguson, Jimerson and Dalton 2001;Jimerson et. al.…”
Section: Introductionmentioning
confidence: 99%